Nilai-Nilai Pendidikan dalam al-Qur’an dan Aktualisasinya - Suparto Iribaram (Al-Riwayah : Jurnal Kependidikan, 2018)
This paper discusses the educational values contained in Q.S. al-Isra' ([17]: 23-25) and its actualization in the modern world. This article shows that, first, the educational values contained in Q.S. al-Isra '(17: 23-25), namely (1) the Aqidah education which Allah obliges His servants to press Him in worship and in worship and forbid them to associate Allah with anything or anyone. Therefore, the one who deserves the highest honors is the one who created nature and everything in it that is Allah Almighty. (2) Education of birrul walidain, after Allah commanded that not worship other than Him then Allah commanded to the Muslims so that they really pay attention to the devotional services to both mothers father and do not regard it as a trivial affair, by explaining that God is the more know what thrilled in their hearts. Second, the actualization of educational values based on Q.S. al-Isra '(17: 23-25) in the modern world, namely (1) education of the creeds in schools should teach the students in union of God that there is no god worthy to be worshiped besides Allah the Almighty God. The limited number of hours of lesson with the tarnished material causes the religious teacher to take the easiest shortcut, that is, to see religious education is no more a lesson than an education. (2) Education of birrul walidain in the modern world today is the treatment of elderly parents is really upside down. When they need more attention from the closest people, especially a child, instead they are mostly alienated from the family on the grounds to get better attention. Finally, they are deposited in nursing homes or others.